PENERAPAN PEMBELAJARAN KONTEKSTUAL MATA PELAJARAN AQIDAH AKHLAK DALAM MENINGKATKAN HASIL BELAJAR SISWA DI MA SUNAN AMPEL NGANJUK - Khoirur Roziqin, Muhamad; Fajar Amrullah, Malik (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
The learning process is an indicator of the success or failure of a learning that is followed by students. A teacher can choose a learning pattern that is by the subject matter to achieve a predetermined goal. A systemic and systematic learning environment can grow and develop the abilities of students. This study aims to investigate the application of contextual learning in Aqidah Akhlak subjects and its impact on improving student learning outcomes. The research method used was a pseudo-experiment with a pre-test and post-test control group design. The research sample involved two groups of grade XI students at MA Sunan Ampel Nganjuk. The experimental group received learning with a contextual approach, while the control group received conventional learning. The results showed that the application of contextual learning in Aqidah Akhlak subjects significantly improved student learning outcomes compared to conventional learning methods. This research contributes to the development of learning methods in the context of religious subjects, especially Aqidah Akhlak. The practical implication of the study is that teachers may consider the application of contextual learning as an effective strategy to improve student learning outcomes in those subjects.